2013
DOI: 10.1039/c3lc41290c
|View full text |Cite
|
Sign up to set email alerts
|

Thinking big by thinking small: application of microfluidic technology to improve ART

Abstract: In Vitro Fertilization (IVF) laboratories often carry a penchant to resist change while in the pursuit of maintaining consistency in laboratory conditions. However, implementation of new technology is often critical to expand scientific discoveries and to improve upon prior successes to advance the field. Microfluidic platforms represent a technology that has the potential to revolutionize the fundamental processes of IVF. While the focus of microfluidic application in IVF has centered on embryo culture, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 68 publications
0
78
0
Order By: Relevance
“…One can envision that other techniques could be adopted in the future, for instance, a device that can perform a gradual in situ change of the medium over time. Such a device might even be used to perform analysis of the media (20,21). A current alternative strategy, however, is to culture the embryo in a single medium that has been optimized to cover the metabolic needs of both early and late-stage embryos during culture.…”
Section: Discussionmentioning
confidence: 98%
“…One can envision that other techniques could be adopted in the future, for instance, a device that can perform a gradual in situ change of the medium over time. Such a device might even be used to perform analysis of the media (20,21). A current alternative strategy, however, is to culture the embryo in a single medium that has been optimized to cover the metabolic needs of both early and late-stage embryos during culture.…”
Section: Discussionmentioning
confidence: 98%
“…Collectively, these experiments using mouse embryos document that microfluidics can be used for preimplantation embryo culture, they provide experimental power in precise regulation of culture environment and informative data on embryo development, and provided benefits for embryo development. There have been numerous reviews discussing the future of microfluidics for domestic animal and human assisted reproduction (Krisher and Wheeler, 2010;Meseguer et al, 2012;Swain et al, 2013). Kieslinger et al (2015) have demonstrated that human embryos can be grown in microfluidic devices, yet to our knowledge, no peer-reviewed published manuscript currently exist demonstrating a benefit of microfluidic embryo culture with human embryos.…”
Section: Embryo Culture With Microfluidicsmentioning
confidence: 99%
“…Among LOC devices, microfluidic sperm sorting (MFSS) chips have been developed and marketed for motile sperm sorting and use two gravity-driven laminar flows across a microfluidic channel of 50-200 µm [52][53][54][55][56][57][58][59][60][61]. Fluids flowing through the semen inlet (A) and the medium inlet (B) move parallel to each other and exit through respective outlets (A→D and B→C) [53].…”
Section: Microfluidic Channel-based Devices For Semen Diagnoses and Mmentioning
confidence: 99%
“…Among LOC devices, microfluidic sperm sorting (MFSS) chips have been developed and marketed for motile sperm sorting and use two gravity-driven laminar flows across a microfluidic channel of 50-200 µm [52][53][54][55][56][57][58][59][60][61]. Fluids flowing through the semen inlet (A) and the medium inlet (B) move parallel to each other and exit through respective outlets (A→D and B→C) [53]. Sperm are then sorted on the basis of their ability to swim across the streamline into the medium stream, and only motile sperm are recovered from outlet C. Using MFSS devices, embryologists can perform a 1-step sorting protocol without centrifugation, and processing can be completed within 30 min [40,[57][58][59][60][61].…”
Section: Microfluidic Channel-based Devices For Semen Diagnoses and Mmentioning
confidence: 99%